2020
DOI: 10.1097/md.0000000000022295
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous MKRN3 nonsense mutation in a Chinese girl with idiopathic central precocious puberty

Abstract: Rationale: Central precocious puberty (CPP) is caused by the premature activation of the hypothalamic-pituitary-gonadal axis. Recently, the makorin ring finger protein 3 (MKRN3) mutations represent the most common genetic defects associated with CPP. However, the MKRN3 mutation is relatively rare in Asian countries. Here, we identified a novel heterozygous MKRN3 nonsense mutation (p. Gln363 ∗ ) causing CPP in a Chinese girl. Patient concerns: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The c.841C>T mutation is located in the CH motif and results in a single amino acid change in the MKRN3 protein. Thus far, 50 MKRN3 mutations associated with CPP have been reported, including 14 frameshift mutations, 27 missense mutations, 4 nonsense mutations and 5 variants in upstream promoter or regulatory regions[ 3 , 5 ]. The current case is only the second report of the c.841C>T mutation in MKRN3 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The c.841C>T mutation is located in the CH motif and results in a single amino acid change in the MKRN3 protein. Thus far, 50 MKRN3 mutations associated with CPP have been reported, including 14 frameshift mutations, 27 missense mutations, 4 nonsense mutations and 5 variants in upstream promoter or regulatory regions[ 3 , 5 ]. The current case is only the second report of the c.841C>T mutation in MKRN3 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this is also the first case of MKRN3 mutation in twin sisters. It is worth noting that mutations in MKRN3 are more common in patients from Western countries than in those from Asian countries[ 3 ], which may result from genetic differences in ethnic groups or the less frequent use of gene testing among children with CPP in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 16 ) reported four pathogenic variants of MKRN 3 in familial CPP. Variants, including whole gene deletions, have been identified since then in > 100 patients with familial and/or idiopathic CPP, the most frequently identified CPP worldwide ( 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ).…”
Section: Makorin Ring Finger Protein 3 (Mkrn3)mentioning
confidence: 99%
“…2 . These variants include a gene deletion, six promoter region abnormalities, and five nonsense, 13 frameshift, and 31 missense variants ( 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ). In vitro studies have shown that the promoter activity of MKRN3 is reduced in variants with promoter region abnormalities than that in wild-type ( 37 , 40 , 42 ).…”
Section: Makorin Ring Finger Protein 3 (Mkrn3)mentioning
confidence: 99%